PELATIHAN E-LEARNING MENGGUNAKAN PLATFORM GOOGLE CLASSROOM DAN MOODLE DI MTS DAN MA SITI KHADIJAH MAJALENGKA - Iik Nurhikmayati; Erik Santoso; Sudianto; Mohamad Gilar Jatisunda (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
E-Learning is a form of learning that utilizes internet facilities in the learning process. The learning process through e-learning can be done anytime and anywhere. This training activity is intended so that trainees get a good understanding of e-learning using the google classroom and moodle platforms. The method of implementing this activity is divided into three main stages, namely planning, implementation and evaluation. Participants in the training consisted of teachers from MTs and MA Siti Khadijah Majalengka. Based on the results of data processing, it can be concluded that e-learning can make learning anytime and anywhere. Based on the results of the processing it was found that 50% of the training participants stated that e-learning was very important and 50% stated it was important. Participants stated that through this training activity an increase in understanding about e-learning, ie 33.3% of participants were very understanding and the remaining 66.7% answered understanding